PLK2 as a key regulator of glycolysis and immune dysregulation in polycystic ovary syndrome - Ma, Hua; Qi, Dahe; Xu, Yating; Shang, Tingting; Si, Yu; Chen, Wenyue; Zhao, Hongting; Ren, Qingling (Frontiers in Immunology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a highly heterogeneous endocrine-metabolic disorder. Ovarian stromal cells influence follicular development and ovulation by secreting cytokines. Glycolysis, a central pathway of glucose metabolism, plays a crucial role in the pathogenesis of PCOS. However, the precise mechanisms underlying dysregulated glycolysis in ovarian stromal cells in PCOS remain unclear.MethodsSeurat and CellChat were employed to analyze single-cell RNA sequencing (scRNA-seq) data, incorporating glycolysis scoring and cell-cell communication analysis. Three independent bulk RNA-seq datasets were integrated to identify key genes. Immune infiltration was assessed using CIBERSORT, ESTIMATE, and ssGSEA algorithms. Functional enrichment analysis (GO, KEGG, and Hallmark) was performed to annotate PLK2-related pathways. Finally, a dehydroepiandrosterone (DHEA)-induced PCOS rat model was constructed to validate the critical role of PLK2 expression in PCOS.ResultsSingle-cell sequencing analysis revealed that endothelial cells in the ovarian stroma of PCOS exhibited the highest glycolytic activity and increased intercellular communication, particularly interacting with fibroblasts via the PPIA-BSG ligand-receptor pair. Integrated transcriptomic analysis identified PLK2 as a central regulatory gene of endothelial glycolysis (AUC > 0.85). Functional enrichment analysis further demonstrated that high PLK2 expression was closely associated with extracellular matrix (ECM) remodeling and promoted chronic inflammation and ovarian fibrosis by activating the NF-κB and IL-17 signaling pathways. Immune infiltration analysis indicated that PCOS patients with high PLK2 expression exhibited enhanced pro-inflammatory responses, increased neutrophil recruitment, and impaired T-cell function, suggesting a shift toward an inflammatory ovarian microenvironment. The DHEA-induced PCOS rat model further confirmed the critical role of PLK2 in disease progression and glycolytic dysregulation.ConclusionThis study establishes PLK2 as a key regulator of glycolysis and immune imbalance in PCOS, highlighting its pivotal role in the metabolic-immune crosstalk within the ovarian microenvironment. These findings suggest that targeting PLK2 may be a potential therapeutic strategy for alleviating glycolytic dysregulation and chronic inflammation in PCOS.